Răspuns :
x + 1/5 = 3/5
x = 3/5 - 1/5
x = (3-1)/5
x = 2/5
9/2 + x = 15/2
x = 15/2 - 9/2
x = ( 15-9)/2
x = 6/2
x = 3
x + 5/7 = 4/3
x = 4/3 - 5/7
x = (28-15)/21
x = 13/21
x = 3/5 - 1/5
x = (3-1)/5
x = 2/5
9/2 + x = 15/2
x = 15/2 - 9/2
x = ( 15-9)/2
x = 6/2
x = 3
x + 5/7 = 4/3
x = 4/3 - 5/7
x = (28-15)/21
x = 13/21
[tex]\dfrac{x+1}{5}[/tex]=[tex]\dfrac{3}{5}[/tex]
5(x+1)=5·3
5x+5=15
5x=15-5
5x=10=>x=[tex]\dfrac{10}{5}[/tex]=2
[tex]\dfrac{9}{2+x}[/tex]=[tex]\dfrac{15}{2}[/tex]
9·2=15(2+x)
18=30+15x
-15x=30-18
-15x=12
x=[tex]\dfrac{12}{-15}[/tex]
[tex]\dfrac{x+5}{7}[/tex]=[tex]\dfrac{4}{3}[/tex]
3(x+5)=7·4
3x+15=28
3x=28-15
3x=13=>x=[tex]\dfrac{13}{3}[/tex]